Internalin B activates nuclear factor-kappa B via Ras, phosphoinositide 3-kinase, and Akt - O'NEILL, LUKE ANTHONY JOHN (The American Society for Biochemistry and Molecular Biology, 2001)
Internalin B (InlB), a 630-amino acid protein loosely attached to the surface of Listeria monocytogenes, participates in the entry of the bacterium into mammalian cells. This process requires the activation of phosphoinositide (PI) 3-kinase by InlB. Previously, we demonstrated that InlB activates the transcription factor Nuclear Factor-kappaB in murine J774 macrophage-like cells, an event that also requires PI 3-kinase. Here we have further investigated this phenomenon. InlB activated the small G-protein Ras in J774 cells. Inhibition of Ras with the farnesyltransferase inhibitor manumycin A inhibited NF-kappaB activation and the recruitment of the p85 subunit of PI 3-kinase, implying that Ras is required for PI 3-kinase activation. InlB also activated the PI 3-kinase downstream effector, Akt, as assessed by increased phosphorylation of Akt on serine 473. Transfection of Hep2 cells with dominant negative Ras N17 or dominant negative Akt inhibited the induction of a reporter gene linked to the interleukin-8 promoter by InlB. Furthermore, the Ras inhibitor manumycin A, the PI 3-kinase inhibitor LY294002, and an Akt inhibitor all blocked the induction of interleukin-8 by InlB. Our study is the first report of a bacterial product activating a pathway involving Ras, PI 3-kinase, and Akt, which leads to NF-kappaB activation. This process could be involved in host defense or the inhibition of apoptosis during infection.
PUBLISHED
Keywords: Biochemistry